(3GdHjGf hGdJhVjM def CNQL dg aj GdUMjM hbO eS HVQH ef GdJLQjMs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdPcQ hMaXg s
(3BNQgG (B:s
(3aQZJ efg jhe GdCMO QGHY GdeMQe SfI JSY hKeGfjf hSHYeGFg s
(3HChdgG NGJe hbajI Ydi ecJHI CMeO HGTG GdLRGQs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B270s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B53 s
Keywords: (3GdJGQjNs